2014
DOI: 10.1177/1087057113497400
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence-Based High-Throughput Screening of Dicer Cleavage Activity

Abstract: Production of small RNAs by ribonuclease III Dicer is a key step in microRNA and RNA interference pathways, which employ Dicer-produced small RNAs as sequence-specific silencing guides. Further studies and manipulations of microRNA and RNA interference pathways would benefit from identification of small-molecule modulators. Here, we report a study of a fluorescence-based in vitro Dicer cleavage assay, which was adapted for high-throughput screening. The kinetic assay can be performed under single-turnover cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…The continuous fluorescence intensity measurement method developed for the Dicer cleavage assay was first reported by Podolska et al (2014) . The principle is illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The continuous fluorescence intensity measurement method developed for the Dicer cleavage assay was first reported by Podolska et al (2014) . The principle is illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the continuous fluorescence intensity measurement method developed by Podolska et al (2014) for Dicer cleavage assays was adopted and modified for monitoring dsRNA degrading activity. Owing to different combinations of fluorophores and quenchers with varying fluorescent intensity ( Podolska et al, 2014 ), selection experiments were performed, which found 5-FAM fluorescent donor- and 3-BHQ1 quencher-labeled 24 bp dsRNA to be the most sensitive substrate. With this substrate, the fluorescence method was validated using traditional gel electrophoresis and a well-accepted micro-quantitative PCR method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was also observed by researchers who carried out a fluorescence-based assay of Dicer cleavage of a long, double-stranded RNA substrate. 32 Thus, tetracyclines may be a better scaffold for the future rational design of potentially selective pre-miRNA binders. Of the remaining small-molecule hits ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Of the nine previously reported compounds that showed inhibitory activity in HTS but were not picked up for dose-response analysis, two were anthracyclines (doxorubicin and daunorubicin), which were reported to interfere with pre-miRNA processing by Dicer (Maiti et al, 2012 ). While our earlier HTS for Dicer inhibitors (Podolska et al, 2014 ) did not identify these compounds (no overlap was found between Bioactives affecting Dicer in vitro and luciferase reporters in vivo ), two other anthracyclines showed inhibitory effects in HTS. One of them (idarubicin) yielded at least three-fold luciferase stimulation in four miRNA-sensitive reporter assays, while it showed a weak stimulation (maximum 2.1-fold) of only one of the three non-targeted reporters (Figure 7B ), which makes anthracyclines interesting candidates for further studies.…”
Section: Discussionmentioning
confidence: 82%